RESEARCH REGARDING THE DEGRADATION OF MEAT SEMI – PRODUCTS AND THEIR CHEMICAL COMPOSITION - Orădan Cristian Adrian; Timar Adrian Vasile (Natural Resources and Sustainable Development, 2024)
The trends in the meat market evolved in the last decade under the influence of consumers’ demands, economic restrictions, and food safety regulations. In this way, there are significant changes related to the quality of raw materials, products, and technologies. The present study tries to answer one of the new issues about the raw materials in meat processing. Due to the national and European regulations that lay down the meat raw material definition, some semi-products like Baader (unnerved meat) and MDM (mechanically deboned meat) are no longer accepted as